Coagulase-negative staphylococci in ewe udder surface and raw milk samples - Tonamo, Andualem; Komlósi, István; Petróczki, Flóra Mária; Peles, Ferenc (Acta Agraria Debreceniensis, 2021)
Coagulase-negative staphylococci (CNS) are among the major causes of subclinical mastitis in dairy ewe flocks. This has a financially significant impact on the ewe dairy sector and consumer health. The determination of the bacterial count, particularly CNS, is critical in terms of the quantity and quality of ovine milk. Thus, the purpose of this study was to quantify the CNS count in the udder surface and raw milk samples of the ewe, in addition to identifying CNS strains (n=8) collected from udder surface and individual raw milk samples by 16S rRNA gene sequencing. A total of 164 samples of udder surface and raw milk originated from four sheep farms were tested. The obtained values were compared between the different farms. Furthermore, values during 2018 and 2019 in the case of Farm I were compared. Significantly higher (p